COMPUTER FORECASTING AND EXPERIMENTAL VALIDATION OF ANTIAGGREGATE PROPERTIES OF CETRINE, GLURENORM, MOEX AND DILTHIAZEM - Nikolay P. Votintsev (Advanced Engineering Research, 2011)
A new algorithm and 'Drug' database, permitting to predict new actions of familiar medical products, are developed and registered. The algorithm is based on comparison of a set of quantum-chemical and geometrical descriptors of molecules through multivariate statistics. The algorithm output for four drugs – cetrine (cetirizine), glurenorm (glividon) , moex (moexipril) and dilthiazem (diltiazem) – was tested through practice.